Ontologi Huruf Nun Menuju Titik Semiotik - Chaer, Hasanuddin; Rasyad, Abdul; Sirulhaq, Ahmad (UI Scholars Hub, 2022)
Semiotics is the study of signs, symbols, and communication in people’s lives. This study which analyzes the letter nun in the Arabic Alphabet using Ferdinand de Saussure’s theory of semiotics, “dyadic semiotics” aims to reveal the breadth and depth of the meaning of the letter nun at the beginning of Surah al-Qalam. This study uses a descriptive method with a content analysis study approach, comprising data collection, data processing, and interpretation. The source of data are the Arabic script. The results of the study show that the ontological symbol for the letter nun is a means of teaching the sign through an established paradigm of semiotics to investigate the meaning element of the letter nun, which is the symbol of the Golden Embryo as a form of symbolic interaction throughout the cosmic order to reproduce and fertilize the world’s egg cell which is symbolized by the cup-like element of the letter nun as the “ovary” and the dot of the letter as a symbol of the fusion between the ‘egg cell and sperm cell’ to become the seed of the eternal universe towards the point of perfection of cosmic semiotic regeneration. All cosmic semiotic processes always occur in all life processes such as the semiotic processes that occur through human reproductive organs such as the testes in males and the ovaries in females in every fertilization process of the zygote. Every order of the cosmos, including human beings, originates from the process of two forms of signs, namely, that which can be seen and observed (signifier) and that which is only to be thought about through ideas (signified).